A study on adult pedestrian severe injuries and fatalities induced by passenger cars in Chongqing, China. (1st January 2015) - Zhao, Hui; Yin, Zhiyong; Yang, Guangyu; Che, Xingping; Xie, Jingru; Huang, Wei; Wang, Zhengguo
A total of recent 187 passenger car–adult pedestrian cases, occurred in Chongqing, China, with 81 severe injuries and 106 deaths, were analysed. The AIS distributions in the head, thorax and abdomen were associated with the severe injuries and deaths, but not in the extremities. The mean ISS of the severe injuries and deaths was 26.3 ± 17.0 and 35.5 ± 17.0. For the severe injuries, 2% occurred at the impact speeds of over 70 km/h and none of the fatal accidents occurred at the impact speeds of lower than 30 km/h. Pedestrians aged over 46 years old and sustaining head injuries have a high fatality rate. The accidents with the impact speeds of over 40 km/h occurring in highways and sunny days carried a high fatal risk. The findings proposed the characteristics of vehicle–pedestrian accidents in Chongqing, China, representing some regional levels in some developing countries.